COVID-19: A commentary on implications for academy football players athletic identity and wellbeing - Maurice, J.; Davenport, T. (Journal of Health and Social Care Improvement, 2020)
On March 23rd, 2020, the UK government instituted a full-scale lockdown in response to the worldwide COVID-19 pandemic. People would only be permitted to leave their homes for the following purposes: 1. Shopping for basic necessities, as infrequently as possible; 2. One form of exercise a day - for example a run, walk, or cycle - alone or with members of your household; 3. Any medical need, to provide care or to help a vulnerable person; 4. Travelling to and from work, but only where absolutely necessary and where work cannot be completed from home. In the days prior to the start of the lockdown, I left a role at one professional football academy based in the North of England and relocated to start a PhD undertaken in conjunction with another professional football academy based in the Midlands. Through doing so, I have had a unique insight into the response of two English football academies to this unprecedented situation. The present article offers a brief commentary on the potential implications of the COVID-19 lockdown for academy players athletic identity and wellbeing. Observations will be presented along with reference to relevant literature in order to draw lessons from the COVID-19 lockdown in the UK for athletic identity, and prepare for future eventualities which share the characteristics of: i) people staying at home; ii) social distancing; and iii) the closure of places of work; in this instance football academies.